2021
DOI: 10.1002/acn3.51276
|View full text |Cite
|
Sign up to set email alerts
|

Type I SMA “new natural history”: long‐term data in nusinersen‐treated patients

Abstract: Objective The aim of this paper was to report the 2‐year follow‐up in type I patients treated with Nusinersen and to assess whether possible changes in motor function are related to the subtype, age, or SMN2 copy number. Methods Sixty‐eight patients, with ages ranging from 0.20 to 15.92 years (mean: 3.96; standard deviation: +3.90) were enrolled in the study. All patients were assessed using the Children's Hospital of Philadelphia Infant Test of Neuromuscular Disorders (CHOP INTEND) and the developmental secti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
41
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 16 publications
6
41
3
Order By: Relevance
“…25 Nusinersen is now available in many countries, with a wider perspective on its efficacy in a range of patient groups, [26][27][28] and some evidence that clinical improvement continues after the first year of treatment. 29 Finally, a recent study assessed the distribution of ASO and the associated SMN Review ll increase in the spinal cord of post-mortem samples from infants treated with nusinersen. This study suggests that there is variability in distribution of ASO within the CNS, with a lower concentration in the cranial portion of the spinal cord and in the brain.…”
Section: Nusinersenmentioning
confidence: 99%
“…25 Nusinersen is now available in many countries, with a wider perspective on its efficacy in a range of patient groups, [26][27][28] and some evidence that clinical improvement continues after the first year of treatment. 29 Finally, a recent study assessed the distribution of ASO and the associated SMN Review ll increase in the spinal cord of post-mortem samples from infants treated with nusinersen. This study suggests that there is variability in distribution of ASO within the CNS, with a lower concentration in the cranial portion of the spinal cord and in the brain.…”
Section: Nusinersenmentioning
confidence: 99%
“…Improvements in motor function may occur beyond the first year of nusinersen treatment, according to 24-month follow-up data from the Italian EAP cohort ( n = 68), with improvements more obvious in patients younger than 2 years of age [ 21 ]. For both CHOP-INTEND and HINE-2 scores, significant ( p < 0.001) improvements were seen from baseline at 12 months, from baseline at 24 months and from 12 months at 24 months.…”
Section: Therapeutic Efficacy Of Nusinersenmentioning
confidence: 99%
“…Real world data have allowed to collect real world data in patients that had not been included in the pivotal studies [37 , 43 , 63-65] . The first published results of the real world usage of Nusinersen, mainly focused on SMA-I patients but with a much wider spectrum of age than those enrolled in the ENDEAR study, confirmed that the best results were found in the younger patients treated before 6 months but significant motor function improvements could also be found in infants treated between 7 and 24 months [66] . A smaller degree of improvement could also be found in the older children.…”
Section: New Therapiesmentioning
confidence: 87%